O repórter Shiva ? práticas discursivas e atividade de trabalho do jornalista em tempo de mudanças - Rodrigues, Marília Giselda (2013)
The current situation of journalism in Brazil and the world is a time of changes, among them, those motivated by new communication technologies, which play an important role in how information is produced and disseminated. Journalism and the traditional journalist lose primacy in news production and compete with multiple communication possibilities and new actors. The impact of technology is also relevant in the daily lives of journalists, since the activities and techniques involved in their work suffer modifications, such as shortening the news production time, the need to understand the various technologies of communication and information increasingly sophisticated, and often the obligation to produce material for different media and formats. This research aims to identify the discursive practices of a community of journalists, in that moment of sharp changes in the profession, on the grounds of french Discourse Analysis and Ergology, the latter understood as an innovative approach of work activities, which allows to combine academic knowledge with the knowledge invested in the activity, revealing values, discourses. The treatment of the discourse from a global semantic (MAINGUENEAU, 1984/2007) assumes that the same determinations of a given discursive formation, its semantic restrictions, are extended simultaneously on the set of discursive plans and all the areas of the discourse, not only the statement, but also the enunciation, and even beyond, institutions, modes of organization of men, all submitted to the same process of structuring. The analysis of the corpus, which brought notes of observation and verbalizations from journalists in their work at Cotidiano section of the daily newspaper Folha de S. Paulo, texts published in issue corresponding to a day of work observed and also texts published on the occasion of reform presented in May 2010, allows grasping some semantic restrictions that permeate both the discourse and the activity of journalists today, and confirms the hypothesis that, compared to traditional journalism, new journalism is journalism that emerges less committed to social responsibility and more involved with entertainment